2021
DOI: 10.3390/app11125592
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality Applications in Industry 4.0 Environment

Abstract: New technologies, such as cloud computing, the Internet of Things, wireless communications, etc., have already become part of our daily lives. This paper provides an insight into one of the new technologies, i.e., augmented reality (AR), as part of the manufacturing paradigm Industry 4.0 (I4.0). The aim of this paper is to contribute to the current state in the field of AR by assessing the main areas of the application of AR, the used devices and the tracking methods in support of the digitalization of the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 116 publications
(171 reference statements)
0
16
0
Order By: Relevance
“…AR remote assistance, such as "see what I see" apps, can provide better knowledge transfer via a peer-to-peer connection that incorporates video, audio, or hand annotations [56][57][58]. Other studies of AR assistance have provided remote technical support, including those for maintenance [52], manufacturing [54,59], automotive [60], and utilities [61], with visual instructions or virtual user manuals [53,55] by means of annotations and content uploaded to phones, tablets, and AR glasses.…”
Section: Video Conferencing and Remote Collaboration With Armentioning
confidence: 99%
See 1 more Smart Citation
“…AR remote assistance, such as "see what I see" apps, can provide better knowledge transfer via a peer-to-peer connection that incorporates video, audio, or hand annotations [56][57][58]. Other studies of AR assistance have provided remote technical support, including those for maintenance [52], manufacturing [54,59], automotive [60], and utilities [61], with visual instructions or virtual user manuals [53,55] by means of annotations and content uploaded to phones, tablets, and AR glasses.…”
Section: Video Conferencing and Remote Collaboration With Armentioning
confidence: 99%
“…A synchronized first-person view offers the same perspective and enables video conferencing or online meetings across devices or platforms through, for example, Webex ® , Google Meet ® , Skype ® , and Zoom ® . In remote collaboration, different AR system approaches have been developed to improve communication efficiency by applying gazevisualization platforms for physical tasks [62], 3D gesture and CAD models of mixed reality for training tasks [63], essential factors for remote collaboration [64], image-or live-video-based AR collaborations for industrial applications [65], remote diagnosis for complex equipment [66], 360 • video cameras (360 cameras) in augmented virtual teleportation (AVT) for high-fidelity telecollaboration [67], web-based extended reality (XR) for physical environments with physical objects [68], Industry 4.0 environments [59], 2D/3D telecollaboration [69], and indoor construction monitoring [70].…”
Section: Video Conferencing and Remote Collaboration With Armentioning
confidence: 99%
“…To put it another way, HRC-based design should be considered more from the perspective of users, including experts. Additionally, more testing in the Workspace area should be conducted [62] to refine control interfaces and minimize stress and fatigue.…”
Section: Human-centered Design Principlementioning
confidence: 99%
“…Among them, AR is a key technology that enriches the real world with contextualized virtual computer-generated information by offering users real-time interaction possibilities [ 1 , 2 ]. Thanks to these capabilities, AR technologies have been adopted in many application areas such as gaming, entertainment, medicine, marketing, the military, and in particular, in the industrial field where AR has been demonstrated to be a valuable tool for improving and accelerating product and process development [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%